Corrigendum and Comments to "Vapor-liquid equilibrium and molecular simulation data for carbon dioxide (CO2) + trans-1, 3, 3, 3-tetrafluoroprop-1-ene (R-1234ze(E)) mixture at temperatures from 283.32 to 353.02 K and pressures up to 7.6 MPa" [Int. J. Refrig. 98 (2019) 362–371]. (August 2019) - Fauve, Rémi; Coquelet, Christophe; Houriez, Céline; Artola, Pierre-Arnaud; Ahmar, Elise El; Rousseau, Bernard
Abstract: We have published vapor liquid equilibrium data (VLE) for the binary mixture of CO2 + R-1234ze(E) (trans-1, 3, 3, 3-tetrafluoroprop-1-ene) in International Journal of Refrigeration, Volume 98, February 2019, Pages 362-371. In this paper, we presented Gibbs Ensemble Monte Carlo simulation data performed at 293.15 K and 353.02 K. It just so happened that there was a mistake in one of the initial configurations at 353.02 K and the results were not correct. We present here corrected MC values and we compare the results with Peng Robinson EoS calculation and REFPROP predictions.